Analisis Job Insecurity dan Motivasi Ekstrinsik Terhadap Kepuasan Kerja - Nurodin, Idang (Baashima : Jurnal Bisnis Digital, Akuntansi, Kewirausahaan, dan Manajemen, 2024)
Human resources play an important role in an organization and the importance of the role of human resources in the operation of an organization can achieve the goals of the company's resources, that is, resources that can achieve the goals of the organization in the future, but everyone's energy and ability are limited. The type of research used in this study is a descriptive method and an associative method with a quantitative approach. The number of samples studied was 137 respondents. In this case, researchers use inferential data analysis techniques, namely multiple linear regression analysis because researchers use more than one independent variable. Based on the results of the study shows that the independent variable has a P-Value value of 0.000 where this probability value is below 0.05. Thus, in accordance with the provisions in the test criteria, if the probability value < 0.05, it can be concluded that the variables job insecurity (X1) and extrinsic motivation (X2) together have a significant effect on employee job satisfaction (Y). Feelings of insecurity felt by employees can reduce job satisfaction. The higher the level of job insecurity, the level of employee job satisfaction tends to decrease. If employees are satisfied, then the desire to leave the organization decreases.